1982
DOI: 10.1159/000250092
|View full text |Cite
|
Sign up to set email alerts
|

Two Years’ Experience with Tigason Treatment of Pustulosis palmo-plantaris and Eczema keratoticum manuum

Abstract: The results are presented of 2 years’ experiments with Tigason® treatment of pustulosis palmo-plantaris (19 patients) and eczema keratoticum manuum (15 patients). These two skin diseases are characterized by being extremely resistant to conventional dermatological therapy, but responding immediately to treatment with Tigason. The rather high frequency of side-effects of the drug (dryness of mucosae, loss of hair, etc.) complicates the treatment but in about 50% of patients continuous or intermittent treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Etretinate has recently been found to be very effective in HDP (Reymann, 1982) but it had to be discontinued in five out of fifteen patients because of side-effects. The present study indicates that PUVA treatment could be an effective alternative to etretinate in severe cases of HDP.…”
Section: Discussionmentioning
confidence: 99%
“…Etretinate has recently been found to be very effective in HDP (Reymann, 1982) but it had to be discontinued in five out of fifteen patients because of side-effects. The present study indicates that PUVA treatment could be an effective alternative to etretinate in severe cases of HDP.…”
Section: Discussionmentioning
confidence: 99%
“…Lowdose maintenance therapy with etretinate at approximately 10-20 mg/day is needed for long-term treatment in order to prevent relapse [4,5], Recently, some new data demonstrated that keratoderma climactericum of Haxthausen's responded well to etretinate [6], In keratosis lichenoides chronica [7], Kyrlc's disease [8] and con fluent and reticulated papillomatosis [9], some rare hyper-and dyskcratotic diseases, etretinate has been reported to produce good results within 3-4 weeks. Concerning its mechanism of action, etretinate inhibits the migration of neutrophilic and eo sinophilic granulocytes by a direct effect on cell motility [10], probably by changing the cells' capability to respond to chemoattrac tants or by modulating components of the epidermis or basal membrane zone to act as chemoattractants.…”
Section: Etretinatementioning
confidence: 99%
“…Palmoplantar pustular psoriasis (PPPP) responds poorly to topical treatment, but it does respond to photochemotherapy with psoralen and UV-A (PUVA) (Morison, Parrish & Fitzpatrick, 1978;Murray, Corbett & Warin, 1980) although the UV-A dose required may be considerable. Oral etretinate has also been used for PPPP (Jansen, Hollmen & Pajarre, 1979), but although there may be improvement few patients actually clear (Reymann, 1982) and an adequate therapeutic action is often limited by unacceptable side-effects. We therefore decided to see whether there was any advantage in combining etretinate with PUVA.…”
mentioning
confidence: 99%